Different Selectivities in the Insertions into C(sp2)−H Bonds: Benzofulvenes by Dual Gold Catalysis Competition Experiments. Issue 42 (28th June 2018) - Plajer, Alex J.; Ahrens, Lukas; Wieteck, Marcel; Lustosa, Danilo M.; Babaahmadi, Rasool; Yates, Brian; Ariafard, Alireza; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K.
Abstract: An unprecedented, often almost quantitative access to tricyclic aromatic compounds by dual gold catalysis was developed. This synthetic route expands the scope of benzofulvene derivatives through a C(sp 2 )−H bond insertion in easily available starting materials. The insertion takes place with an exclusive chemoselectivity with respect to the competing aromatic C−H positions. A bidirectional synthesis with two competing ortho ‐aryl C−H bonds in the selectivity‐determining step also shows perfect selectivity; this result is explained by a computational investigation of the two conceivable intermediates. The intramolecular competition of two non‐equivalent aryl C−H bonds with a benzylic methyl group also showed perfect selectivity. Abstract : Which one to pick? The highly reactive vinylidene intermediate, which is generated in situ by a dual activation mechanism, with high selectivity reacts with one out of several non‐equivalent C−H bonds. This principle can be extended to a perfectly selective bi‐directional synthesis of extended π‐systems.